THE FORMATION OF SCIENTIFIC THINKING OF GRADUATE STUDENTS (Multidisciplinary Journal of Science and Technology, 2025)
The article is  devoted to  the  study of  the  problem of  the  formation of  scientific thinking among graduate students in  psychological-pedagogical field of training. The theoretical review analyzes the research of foreign and Russian authors from various points of  view covering this problem. The d-efinition of scientific thinking is given as a type of intellectual activity conditioned by a specific motivation of a person and representing the process and result of  solving a  scientific problem, which consists in  building an  algorithm for its solution. The  methods and conditions contributing to  the  formation of  scientific thinking of  graduate students are  considered. The results of an empirical study of the masters’ understanding of the specifics of scientific thinking and attitudes towards it are presented.